PENERAPAN LEAN SIX SIGMA UNTUK MENINGKATKAN KUALITAS PADA PERUSAHAAN PERCETAKAN TEKSTIL - Vioren, Venny; Kosasih, Wilson; Doaly, Carla Olivia (Universitas Tarumanagara, 2024)
In order to face the competitive market, companies are required to produce good quality products and maintain their quality to meet customer expectations. The research was conducted at one of the textile printing companies in Indonesia with the object of research, namely CVC (Chief Value Cotton) fabric. This research aims to find out and overcome the company’s problems using Lean Six Sigma method with DMAIC completion stages to improve the quality of the fabric printing process and reduce waste in the company. Define phase started by identificating the company’s problem and measure phase maps the current value stream mapping and calculate process cycle efficiency (PCE) with a result of 17.88%, defects per million opportunities (DPMO) with a result of 16,627 and sigma level of 3.63 sigma. The next step is to analyze the causes of defective CVC fabric using fishbone diagrams, pareto diagrams, and why-why analysis. The last is control phase by monitoring the implementation of proposed improvements and recalculating process capabilities.